2016
DOI: 10.1007/s00127-016-1315-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of group memberships predicts depression in postpartum mothers

Abstract: The social identity model of identity change provides a useful framework for understanding postpartum depression. Interventions to prevent and treat postpartum depression might aim to support women in maintaining important social group networks throughout pregnancy and the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 55 publications
9
87
1
Order By: Relevance
“…It is clear that physical distance and time difference can also make it hard to maintain previously important social identities (e.g., with family and friends at home). If old support networks fall away, this tends to exacerbate feelings of identity loss that have been found to be problematic for people going through other life transitions (Haslam et al, ; Iyer et al, ; Seymour‐Smith et al, ). In the present case, it was clear that this contributed to a sense of social isolation and loneliness and that this undermined students' well‐being in ways previously discussed by Cruwys et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that physical distance and time difference can also make it hard to maintain previously important social identities (e.g., with family and friends at home). If old support networks fall away, this tends to exacerbate feelings of identity loss that have been found to be problematic for people going through other life transitions (Haslam et al, ; Iyer et al, ; Seymour‐Smith et al, ). In the present case, it was clear that this contributed to a sense of social isolation and loneliness and that this undermined students' well‐being in ways previously discussed by Cruwys et al ().…”
Section: Discussionmentioning
confidence: 99%
“…This found that individuals who had more group memberships prior to their stroke were more likely to maintain some of those group memberships after it and that this was a basis for them to report greater well‐being than those who initially had fewer group memberships. Other studies have provided further support for SIMIC in the context of other life transitions—notably becoming a mother (Seymour‐Smith, Cruwys, Haslam, & Brodribb, ) and retiring from work (Steffens, Cruwys, Haslam, Jetten, & Haslam, ). A recent longitudinal study of international students informed by SIMIC also found that those students who experienced a loss of social identity as a result of the transition experienced subsequent decline in well‐being (Praharso et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…In line with these perspectives, social neuroscience research has revealed physiological and psychological benefits of greater SGMs and negative effects of social threat and exclusion . The Social Identity Model of Identity Change (SIMIC) asserts that major life transitions, particularly those involving loss of social groups, negatively impact on psychological well‐being . For example, research on people with stroke found that greater subjective cognitive impairment was associated with loss of SGMs, which in turn predicted poorer psychological well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…These include models which posit that social relationships fulfil a fundamental psychological need for belonging (e.g., Baumeister & Leary, 1995) and, more recently, the social identity approach to health (or the "social cure" perspective, Jetten, Haslam & Haslam, 2012). This perspective states that our social relationships (and in particular, our social group relationships) act as psychological resources that protect one's health, particularly in times of adversity (see for example, Praharso, Tear, & Cruwys, 2017;Seymour-Smith, Cruwys, Haslam & Brodribb, 2017).To summarise, the dominant public health and epidemiological perspective on social connectedness is that it is a resource (a form of capital) that an individual can draw upon in times of need, and which will protect their mental health. …”
mentioning
confidence: 99%